The formation of value orientations in teenagers under the language teaching process - Kavakli, Mehmet; Dauletbekova, Zhanat; Issayeva, Zhazira; Semiz, Kenan (Opción, 2020)
This article deals with the ways how to build value orientations in adolescents. Textbooks of the Kazakh language for grades 5-7, which are taught in Kazakstan, were studied in the context of the value formation among students as a method. As a result, Stability and non-contradiction of value orientations allow the development of such personal qualities as determination, reliability, devotion to one’s positions and ideals, and activity in one’s life position. In conclusion, the most necessary requirement for the adolescence period is the subject of a child’s activity is the teenager himself or herself.